The Role of the Visum Et Repertum in the Investigation Process of Crime of Maltreatment - Haryono, Tri Agus; Rosidah, Rosidah; Permana, Diki; Bunyamin, Bubun; Yuliarpan, Pipit; Hernawati, Hernawati (Formosa Journal of Applied Sciences, 2025)
Visum and repertum are two very important documents in the legal process, especially in cases of maltreatment. The medical data contained in these documents can be used as evidence that cannot be doubted in court. In addition, the visum and repertum can also assist the authorities in determining the next steps in handling the case. From the results of the research conducted, it can be concluded that the visum and repertum have a very important role in the investigation and law enforcement process. This document can be key in prosecuting perpetrators of abuse and providing justice for victims. Therefore, it is very important for the authorities to always examine the information contained in the visum and repertum carefully and thoroughly so that the legal decisions taken can be more fair and in favor of the victims of persecution.